Effects of Gender on Costly Punishment. (12th April 2017) - Mieth, Laura; Buchner, Axel; Bell, Raoul
Abstract: Women are often believed to be more cooperative and less egoistic than men. In the present study, we examined whether people punish women for failing to live up to these benevolent gender stereotypes. Participants played a prisoner's dilemma game with female and male partners who either cooperated or defected. Participants were offered a costly punishment option. They could spend money to decrease the payment of their partners. In Experiment 1, participants spent more money to punish the defection of female in comparison to male partners, but this effect of partner gender on punishment was indirect rather than direct: Participants were more likely to cooperate with female partners than with male partners, which gave them more opportunity for moralistic punishment. In Experiments 2 and 3, we examined the effects of the participants' own gender on cooperation and punishment of female and male partners. Female participants cooperated more with female partners than with male partners while male participants treated female and male partners equally. We conclude that the effect of facial gender on punishment are indirect rather than direct. The results also showed that women, in contrast to men, tended to make decisions that can be considered more social and less rational from an economic point of view, consistent with social‐role theory and evolutionary accounts. Copyright © 2017 John Wiley & Sons, Ltd.